IMPLEMENTASI PERMAINAN PUZZLE DALAM MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK USIA DINI - Sri Utami (I'tibar: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This research examines the cognitive development of early childhood through puzzle games at Pertiwi Indralaya Kindergarten. Using a descriptive qualitative approach, this research involved participant observation, semi-structured interviews, and documentation analysis. Four children aged 4-6 years with different levels of cognitive development were observed for six weeks. The results showed significant improvements in cognitive aspects such as problem solving, spatial understanding, classification, and creativity. Children who were initially ???Best Developing??? (MB) showed great improvements in perseverance, problem-solving strategies, and classification abilities. Meanwhile, children who were initially ???Best Developing??? (BSB) developed high-level cognitive abilities. These findings support Piaget and Vygotsky's cognitive development theories, as well as previous research on the role of puzzle games in child development. This research concludes that puzzle games are an effective method for stimulating and improving various aspects of early childhood cognitive development.